Comparative assessment of co2 emissions and fuel consumption in a stationary test of the passenger car running on various fuels - Jaworski, A.; Boichenko, Sergii; Madziel, Maksymilian; Pavliukh, Lesia (Science-based technologies, 2020)
Introduction. The main goal of the development of the transport sector is to reduce the emission of pollutants to the environment, including CO2, which is particularly important due to global warming. CO2 emissions are directly related to fuel consumption. In addition, CO2 emissions are also related to the type of fuel used in transport. Problem statement. Efforts are being made to reduce CO2 emissions and fuel consumption by improving the design of cars and engines to reduce energy consumption in road traffic, including by recovering some of the energy of lagging traffic in hybrid and electric drives. CO2 reduction can also be achieved by using alternative fuels, hydrogen being the most preferred. Research methodology. The analysis was carried out for a passenger car. Based on the technical data of the car, road traffic energy consumption was calculated in the NEDC stationary test. Results and discussion. The article presents a comparative analysis of fuel consumption and CO2 emissions for the passenger car with an internal combustion engine powered by traditional and alternative fuels. The analysis was developed on the NEDC test. On the basis of the calculated resistance to motion and energy consumption of motion, as well as for the actual results of tests carried out on the chassis dynamometer of a car powered by gasoline and diesel fuel, approximate values of the engine efficiency were determined. Then, calculations of CO2 emissions and fuel consumption were carried out for the following: CNG, LPG, ethanol, methanol and E85. Conclusions.As it results from the research carried out for individual UDC and EUDC phases, fuel consumption and CO2 emission are not in each case directly proportional to the energy consumption of the car movement.The best hydrocarbon fuel for CO2 reduction from the internal combustion engines is natural gas (CNG). CO2 emission, assuming the same engine efficiency as when fueled with petrol, is lower in relation to fueling with petrol by approx. 16% for the analyzed car.